DFT Analysis of Ethanol Electro-Oxidation on Fe(110) and Fe3C(110) and its Correlation with the Stress Corrosion Cracking of Carbon Steel. Issue 11 (27th July 2020) - Ashrafriahi, Ali; Foroozan, Amir; Ghaznavi, Mahmoudreza; Seifitokaldani, Ali; Newman, Roger C.
Abstract : Striking mechanical and morphological similarities of the stress corrosion cracking (SCC) of carbon steel in ethanolic media with those governed by a cleavage-like mechanism in CO-CO2 aqueous solutions, prompted the investigation of the possibility of ethanol electrochemical oxidation into CO on ferrite (Fe) and cementite (Fe3 C) surfaces. Density functional theory computations on (110) surfaces reveal that the catalytic activity of Fe and Fe3 C through the α dehydrogenation pathway can significantly reduce the energy barrier of electro-oxidation of ethanol and production of CO to 0.575 and 0.480 eV, respectively. These first principle calculations indicate that at the anodic potentials applied during potentiostatic slow strain rate testing, ethanol electrooxidation to CO is thermodynamically viable on carbon steel, giving further credit to the involvement of cleavage type SCC of carbon steel in ethanolic environments.